(untitled) (Journal of the College of Basic Education, 2022)
In the name of God, and prayers and peace be upon the Messenger of God, and praise be to God, Lord of the worlds, we praise Him, we seek His help, we seek guidance from Him, and we seek His forgiveness, we seek refuge in God from the evils of ourselves and from the evils of our deeds, whoever God guides will not misguide him, and whoever he misleads you will not find a guiding guardian for him, after that.In this religious research that I put in the hands of your presence, I am discussing an important religious jurisprudence issue in the Muslims’ belief and their lives, which is (precautionary prayer), and the provisions it contains, for example: the conditions that must be met in it in terms of how to perform it, and other provisions related to it mentioned In the issue, which every Muslim, male and female, must be keen to learn, and I relied in this research on the mothers of jurisprudence books of the Imami school of thought, in investigating the issue. To arrange it on the introduction, the study section, and the investigation section, where I made my work in it composed of two parts, as follows: The study section, which is composed of a topic, the first topic: introducing the author’s life, and it included six demands, the first requirement: his name and lineage, the second requirement: his titles and family The third requirement: his birth and death, the fourth requirement: his travels, the fifth requirement: his elders and disciples, the sixth requirement: his travels, the second topic: the verified text, the first requirement: a description of the manuscript copies, the second requirement: the name of the manuscript and documenting its attribution to its author, and the reason In his authorship, and the third requirement: methodological investigation. And the third topic: is the verified text, from the manuscript (Nafias Al-Masaa’il), the issue of (Salat Al-Ihtiyat) (1). The purpose of my research is for the Muslim to know how to worship correctly, following the Sunnah of the Prophet - may God bless him and his family and grant him peace - and I do not conceal from you that delving into religious issues is a vast matter, and a vast sea, and it is our duty as Muslims and researchers to understand its aspects and learn the fundamentals of our religion. And from this idea, I came up with the idea of my research, so that my message would reach everyone who wants to benefit and learn more about his religion.